Planktonic foraminifera ba/ca as productivity proxy in western South Atlantic - Albarracin, Paula; García Chapori, Natalia; Cecilia Laprida; Martín, Rodrigo Sebastian; Díaz, Germán Ricardo; Groeneveld, Jeroen
Planktonic foraminifera are marine microorganisms that play a crucial role in paleoceanographicreconstructions. The measurement of trace elements and their ratios in foraminiferal shells have provento be valuable proxies for studying past oceanic conditions. In particular, the Ba/Ca ratio has been linkedto various environmental conditions such as surface primary productivity, seawater Ba concentrationand fresh water input. Therefore, the calibration between the Ba/Ca ratio and the parameter to bereconstructed results essential for robust interpretations of past oceanographic parameters and climateconditions. Accurate calibrations enhance not only our understanding of historical oceanic conditions,but also the role of trace elements in marine ecosystem.This study focuses on analyzing surface sediment samples from the western South Atlantic between33°S and 47°S to assess the potential of Ba/Ca ratios measured on planktonic foraminifera as apaleoproductivity proxy. In order to do this, non-encrusted shells of Globoconella inflata were carefullycrushed and cleaned following the standard cleaning procedure for trace elements analysis offoraminifera. Export productivity flux data (molC/m2/yr) were obtained from the SIMPLE-TRIM model forthe same samples, and hence a regression analysis was applied.Our results revealed a positive correlation (r2=0.53) between the Ba/Ca ratios and the productivity fluxdata highlighting its potential use as a proxy of paleoproductivity in the region. Higher Ba/Ca ratiosmeasured in G. inflata correspond to sites of higher productivity, while lower ratios correspond to siteswith lower productivity. A positive correlation between export production and Ba/Ca ratios has also beenrecorded on N. dutertrei and P. obliquiloculata shells from sediment traps and core-top samples of theEquatorial Pacific suggesting that increased Ba/Ca ratios in the non-spinose species are the result ofcalcification occurring in Ba-enriched particulate organic matter.The results obtained here contribute to refine the ...